Older people in the shadow of the social care market: European social models, policy dilemmas and practice challenges concerning the crisis in long term care - Stepney, Paul (Ревија за социјална политика/Journal of Social Policy, 2020)
The full extent of the crisis in long term care (LTC) was cruelly exposed by the recent spread of the corona virus throughout Europe, highlighting the vulnerability of many frail older people especially in care homes. The object of this article is to unravel the nature of the crisis in LTC, assess its impact on older people and analyse the challenges facing policy makers and practitioners. The UK provides a primary focus as its community care reforms have set a benchmark for reform elsewhere in Europe. Hence, its mixed economy of provision, overt consumerism and use of the market to contain costs will be subject to critical scrutiny. Reference will be made to policy in other European welfare states and the challenges raised by recent EU reports on LTC, to meet the needs of Europe’s ageing population. Different welfare models will be assessed to establish which policy framework delivers the most effective and integrated care services for vulnerable older citizens. The debate will be illustrated by examining contemporary issues of concern, such as, hospital discharge of older people, risk management dilemmas in practice and escalating cost of LTC. In this article an interpretive approach to knowledge production is adopted drawing on documentary sources, including case studies, official reports and empirical research evidence. Analysis does not follow a strict comparative design, but reflects a more investigative essay. It was found that while a focus on risk continues to shape mainstream practice, there is increasing recognition of the need to develop more extensive community based LTC with an emphasis on prevention and empowerment. There is good research evidence for investing in rehabilitation, integrated provision and person-centred home care for older people. The article concludes with a practice recommendation to this effect.